Obstacles to the participation of a university student in volunteer work – A field study, applied to female students of King Saud University – - Al- Bogmay, Naifah Munahi; Al- Bardisi, Mardia Mohammed (Journal of Humanities & Social Sciences, 2021)
The study Obstacles to the participation of the university student in the study A field study applied to the students of King Saud University and their point of view in order to study about those obstacles, and to achieve the goal of the study, the use of the researcher, the descriptive approach. 3.00) with a verbal estimate (2.12 out of 3) with a verbal estimate (somewhat disabled). (2.29 out of 3), followed by the student- related handicaps and she got a mean (1.95) and the two fields with verbal grade (somewhat disabled). The two fields are verbal esteem (somewhat handicapped). The third axis happened; Suggestions for appropriate methods to activate volunteer work on a year average (2.77) with a verbal estimate (agree). In light of the results, a set of recommendations and proposals were presented at the conclusion of the study to address these obstacles.